Sistem Tracer Study dan Monitoring Alumni Universitas Pamulang - Heri Haerudin; Ari Syaripudin; Dimas Abisono Punkastyo; Farida Nurlaila; Joko Riyanto (Teknik Informatika Universitas Pamulang, 2020)
In the implementation of higher education, of course, the relevance of the curriculum is needed in improving the quality of learning. One of the efforts to fulfill this is through alumni tracking (tracer study). Tracer study is a strategy that allows higher education institutions to obtain input on adjusting the curriculum to current industry needs so that it can become the basis for future improvements. Lack of distribution and collection of questionnaires again became a problem for the tracer study team, because during its implementation there was little response from alumni and stakeholders. Therefore we need a system that can be used to collect and manage and present data accurately from the measurement results of the tracer study in the form of parameters such as work status, job relevance, level of importance of educational services, level of satisfaction of educational services, and the influence of thesis quality. As well as measuring the level of stakeholder satisfaction with alumni with parameters in the form of ethics and morals, expertise based on scientific fields, skills in communication, and teamwork. The results showed that the process of collecting and processing tracer study instruments according to the parameters required in the accreditation process was easier to do because it was website-based. Besides, it made it easier for alumni and stakeholders to fill out the questionnaire, so that more feedback was obtained by the tracer study team.